Endometrial compaction does not predict the reproductive outcome after vitrified–warmed embryo transfer: a prospective cohort study. Issue 1 (July 2022) - Olgan, Safak; Dirican, Enver Kerem; Sakinci, Mehmet; Caglar, Mete; Ozsipahi, Arif Can; Gul, Saniye Merve; Humaidan, Peter
Abstract: Research question: Does endometrial compaction, determined by both transvaginal (TVUS) and abdominal ultrasonography (AUS), improve reproductive outcomes in vitrified–warmed embryo transfer (FET) cycles, and is there a correlation between compaction and serum progesterone concentrations on day of embryo transfer? Design: Prospective observational cohort study at a single tertiary care IVF centre including 204 patients undergoing high-quality vitrified–warmed blastocyst transfer in a hormone replacement therapy (HRT) cycle. The change in endometrial thickness (EMT) between end of oestrogen-only phase and day of embryo transfer, as measured by sequential TVUS, was used to categorize endometrium as undergoing compaction (≥5% decrease), no change, or expansion (≥5% increase). EMT was also examined using AUS at the time of embryo transfer. Primary outcome measure was ongoing pregnancy rates. Results: Thirty-one cycles (15.2%) demonstrated compaction, whereas 123 (60.3%) expanded and 50 (24.5%) remained unchanged as measured by sequential TVUS. Ongoing pregnancy rates did not differ among cycles with compaction (58.1%), those with expansion (56.9%), and those with no change (60.0%; P =0.932). Furthermore, oestrogen, progesterone and oestrogen/progesterone concentrations on day of embryo transfer were comparable among all groups. Using AUS, endometrial compaction was seen in 46 cycles (22.5%), and there was a positive correlation between body mass index and AUS-measured EMT change (ρ = 0.161, P = 0.021). In the group with AUS-determined endometrial compaction, AUS measurements showed a significantly thinner EMT on day of embryo transfer (8.3 mm; interquartile range [IQR] [7.5; 9.2] versus 9.3 mm; IQR [8.4; 11.4], P < 0.001) and higher for EMT change (1.3 mm; IQR [0.8; 1.7] versus 0.1 mm; IQR [–1.1; 1.0], P < 0.001) compared with TVUS measurements. Conclusions: Endometrial compaction during HRT–FET does not predict ongoing pregnancy.